FURTHER OBSERVATION ON NEWLY LOCATED PRAWN FISHERY OF SAURASHTRA COST - GOPALAN, U K (Fishery Technology, 2025)
The abundance of prawns in a newly located ground offSaurashtra has been described. Catch composition showed thatMetapenaeus a{finis formed the bulk of the catches. Previously thisspecies was thought to be of not much commercial importance inthis region. The peak of the fishery lasted from September toNovember. Observations on the biology of this species showed thatit occurs as an independent stock in this region. The significance ofthe gear employed in fishing is also emphasized.